MODEL DAN RANCANGAN EVALUASI PROGRAM BIMBINGAN DAN KONSELING - Siti Wahyuni (IAIN Padangsidimpuan, 2017)
Evaluation is an attempt to obtain information on a regular, continuous, and comprehensive basis of the process and outcomes of the development of attitudes and behaviors, or the developmental tasks of the students through the program activities that have been implemented. Evaluation or assessment is an important part in the management or management of the implementation of guidance and counseling in accordance with the developments that occur both in the overall school program, social development and the challenges that occur in education so the program of guidance and counseling services should not be static or it to it. Similarly, from the development of the program itself, a program of guidance and counseling services needs to be developed and improved so that it can be designed and realized in accordance with the development needs of learners as one of the target service. Even if the evaluation service is not a direct service to the student, the evaluation will have an impact on the improvement of the services required by the student. So that in the end students can feel the impact of improvement or changes in accordance with the dynamics of aspects developed in a program.The model of evaluation arises because of continuous explanation efforts derived from human development and desire to try to apply the principles of evaluation on a more abstract scope including in the fields of education, behavior and art. In this paper we will present some models that can be used in the evaluation of guidance and counseling programs, ie goal attainment evaluation model, formative and summative evaluation model, responsive evaluation model and CIPP evaluation model (Context, Inputs, Process and Product). Some things to consider in designing evaluation of guidance and counseling programs are: title of activities, reasons of implementation, general goals and specific objectives, evaluation questions, methodologies used and procedures and steps of evaluation activities.Keywords: Evaluation, model, and design.